2018
DOI: 10.1016/j.chieco.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

China and international housing price growth

Abstract: We document the Chinese effects on international residential property price growth. We show faster growth of the housing prices associated with larger decline in recent past growth of China's GDP, larger increases in China's savings rate, or stronger rise in China's risks. These results are consistent with the notion of Chinese investing in overseas property markets when faced with less promising investment opportunities at home and when they have the means to invest offshore. These effects are stronger for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
(1 reference statement)
2
7
0
Order By: Relevance
“…This paper also supports the finding of Lin et al (2018) that population growth has a promoting effect on urban house prices, as well as that of Liu (2023) that the size of loans has a promoting effect on house price growth. Additionally, this paper finds that FDI promotes house price growth, which is consistent with the works of Chang et al (2018) and Ahmed and Jawaid (2023), further validating that FDI is one of the factors affecting house prices. Moreover, the coefficients for Pgdp and Population were 0.1398 and 0.1681, respectively, suggesting that urban economic development and population size have a greater impact on housing prices compared to FDI, loans, and industrial structure.…”
Section: Baseline Regression Resultssupporting
confidence: 86%
“…This paper also supports the finding of Lin et al (2018) that population growth has a promoting effect on urban house prices, as well as that of Liu (2023) that the size of loans has a promoting effect on house price growth. Additionally, this paper finds that FDI promotes house price growth, which is consistent with the works of Chang et al (2018) and Ahmed and Jawaid (2023), further validating that FDI is one of the factors affecting house prices. Moreover, the coefficients for Pgdp and Population were 0.1398 and 0.1681, respectively, suggesting that urban economic development and population size have a greater impact on housing prices compared to FDI, loans, and industrial structure.…”
Section: Baseline Regression Resultssupporting
confidence: 86%
“…Finally, we likely provide preliminary evidence for an alternative explanation of the surge in Chinese OFDI (or, by and large, OFDI from emerging markets): Chinese firms took advantage of the rare opportunity provided by the government to transfer assets overseas through CBAs (Buckley et al , 2018; Chang et al , 2018; Gunter, 2017). The rapid surge in OFDI from emerging markets has prompted scholars to find new theories on internationalization.…”
Section: Introductionmentioning
confidence: 86%
“…Buckley et al (2018) identified this topic as a critical area for future research and emphasized that “the use of FDI as a cover for capital flight is growing” (p8), e.g. investment in tax havens (Buckley et al , 2015) and foreign real estate (Chang et al , 2018).…”
Section: Literature Methods and Hypothesesmentioning
confidence: 99%
“…Low interest rates, the risk of rising inflation, and the globalisation of real estate markets also sparked a heightened interest in the housing market among both lay and professional investors (e.g. Rogers & Koh 2017 ; Chang et al, 2018 ; McKenzie & Atkinson, 2020 ; Hamnet & Reades 2019 ; Wijburg & Aalbers 2017 ). The result–the increasing financialisation of housing (e.g.…”
Section: Introductionmentioning
confidence: 99%